SISTEM INFOMASI SALES FORCE BERBASIS MOBILE COMPUTING PADA PT.NATA BANGUN PRIMA BEKASI - Anastasia Siwi Fatma Utami; Sari Hartini (Paradigma, 2012)
Development of information technology and the technology of the Internet resulted in a collaboration that can support the effectiveness of the data processing, distribution, data or information that can assist in the process of the activities conducted by acorporation, one of the activities that can take advantage of computer technology and the Internetisthe business of selling,Sales activityis an activity that interacts directly with consumers to obtain or ders or sales, so it is necessary speed and accuracy in the presentation of information. Build PT.Nata Prima is one company that is selling one of the activities in support of the company's sales process has be enaided by the information system but as the running time, mobility PT. Nata Bangun persadasales activity is very high so that the system information contained in the company can no longer handle, demands that information system scan run more practical and can be done any where, quickly and easily, the application that can run on mobile devices. Applications Sales Force via mobile is an application that is run by using an Internet connection is made on the need to support the sales force applications that are already available today, which are expected to conduct employee approval unlimited space and time. The benefits to be gained from this research. There fore with a computerized system of mobile applications or mobile computing are expected to be better and can be run more effectively and efficiently treateasily usedby the employees or the management company.Keywords: mobile computing, Sales Force , information system